Learning object for education with AR and hand gesture recognition - Sean Senn, Pow Chiok (2019)
Augmented Reality (AR) allows us to interact with the world and unlocking information and experiences by simply pointing our smartphone at any image, object or location. Over the past several years, AR applications becoming more popular and widely available in the smartphones. This project will show the implementation of gesture recognition to Augmented Reality to help improve the current AR technologies to interact with the realworld motion such as hand movements. This enable the users to make use of Augmented Reality to learn and explore in a different way. By implementing gesture recognition to Augmented Reality, the education method can become interesting and learn better using 3-D objects because it is visualized and the user able to interact with the objects. The project is build using Unity 3D and developed based on ManoMotion SDK. The methodology used in this application development is Rapid Application Development model.